(untitled) - Pokhrel, Subodh (Can Tho, 2020)
Mekong Delta of Vietnam is the prominent area of the striped catfish (Pangasianodon hypophthalmus) production and remains the top exporters in the world. However, diseases have been one of the significant problems for theprofitability of striped catfish farming in the area stated. Basic surveillance was carried out in the major striped catfish culture areas in An Giang Province and Can Tho city during the year 2019, 2018, and 2017 with an objective of mapping disease occurrences, disease types, causative agents, and parasites using GIS. Forty, thirty-three, and twenty-nine different cases were collected in the year 2019, 2018, and 2017 respectively from the study area. 17 other cases occurred in An Giang and Can Tho city were provided by Can Tho Sub-aquaculture Department. Clinical diagnosis and the differential diagnosis were performed on the farm and samples were transported to the aquatic pathology lab of CAF, CTU.
Keywords: Fish culture,Nuôi cá; Research,Nghiên cứu